Measuring the Selection of Pay Referents: A Methodological Analysis of the Questions on Pay Referents in the 2008 and 2009 SOEP Pretest Modules - Simone Schneider; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Income comparisons are among the key mechanisms used to explain satisfaction and happiness, among other outcomes. Yet progress on the questions of who people use as social referents and whether differential selection patterns exist can only be made based on valid and reliable measures of pay referents included in large-scale population surveys. The German Socio-Economic Panel Study (SOEP) is pursuing this task through two questions on pay referents introduced in the 2008 and 2009 pretest modules of the SOEP. This paper analyses the quality of the two questions on pay referents in the 2008 module and discusses potential for improvement through modifications of the questions in the 2009 module. The paper concludes that the difficulties in answering questions on pay referents were not completely overcome in the 2009 pretest. To provide more solid evidence on potential biases in response behavior, the paper suggests the inclusion of reliable instruments for measuring personal dispositions.
Keywords: D31; D63; Z13; 330; income comparisons; relative income; reference groups; SOEP